Multidrug resistance phenotype in patients with chronic lymphocytic leukemia as detected by immunofluorescence (FACS) and Northern blot analysis - Wulf, Gerburg; Kluding-Münch, Hildegard; Ho, Anthony Dick; Dörner, Maria; Döhner, Hartmut; Manegold, Christian; Hunstein, Werner (Leukemia research, 1994)
The multidrug resistance (MDR) phenotype has been demonstrated to be related to the overexpression of P-glycoprotein, a 170 kDa transmembrane efflux pump. We studied P-glycoprotein expression in 40 patients with chronic B-cell leukemias by FACS analysis using MoAb c219, which recognizes both the MDR1 and the MDR3 gene product. We found significantly elevated P-glycoprotein expression in these patients as compared with normal controls. Patients who had received previous chemotherapy regimens containing MDR-related drugs showed significantly higher P-glycoprotein expression with MoAb c219 than those patients who had been untreated. Northern blot analysis of MDR1 and MDR3 gene expression in 32 of the patients gave a similar result: in the analysis of total RNA four of six patients (66%) pretreated with either vinea alkaloids or anthracyclines were MDR1 positive as opposed to 6 of 26 (23%) who had no treatment or treatment without these agents. In contrast, MDR3 expression was found more frequently (63%), but was randomly distributed in the differently treated groups. Increasing the sensitivity level by analysis of enriched mRNA (polyA + RNA) led to the detection of MDR1 and MDR3 expression all B-CLL patients. We conclude that a basic elevated P-glycoprotein expression is intrinsic in CLL cells, which is possibly upregulated under chemotherapy. This might be responsible for initial and acquired chemotherapy resistance in CLL patients. Follow-up of the B-CLL patients over 46 months showed that the median survival time for MDR1+ patients was 19 months as opposed to 46 months for MDR1- patients (p < 0.01). There was no statistical difference in survival between MDR3+ and MDR3- patients. In the MDR1+ group, eight of nine patients had developed resistance to the therapy with MDR-related drugs. The expression of MDR1 might, therefore, predict treatment failure with MDR-related drugs and be a negative prognostic factor.